Risk Factors for Fetal Death and Maternal AP Severity in Acute Pancreatitis in Pregnancy - Shi, Xiaolei; Hu, Yuepeng; Pu, Na; Zhang, Guofu; Zhang, Jingzhu; Zhou, Jing; Ye, Bo; Li, Gang; Ke, Lu; Liu, Yuxiu; Yang, Qi; Tong, Zhihui; et al. (Frontiers in Pediatrics, 2021)
Background: Acute pancreatitis in pregnancy is a rare but highly life-threatening gestational and perinatal disease. Objective: This study aimed to identify the risk factors for fetal death and acute pancreatitis severity. Methods: This retrospective cohort study enrolled patients with acute pancreatitis in pregnancy in our center from January 1, 2012, to August 1, 2020, and classified them according to two clinical endpoints, fetal outcome and disease severity. The groups were examined and compared according to gestational week, etiology, gravidity and parity, complications in pre- and post-delivery, and medical history. Logistic regression analysis was performed to identify the independent risk factors for fetal death and acute pancreatitis severity. Results: Of the 90 enrolled patients, 28 (31.1%) had fetal death and 43 (47.8%) had severe acute pancreatitis. Logistic regression analysis showed that pre-delivery acute respiratory distress syndrome (OR, 5.8; 95% CI, 1.5–22.4; P=0.010) and gestational week (OR, 0.9; 95% CI, 0.8–1.0; P=0.010) were risk factors for fetal death. Gestation week (OR, 1.2; 95% CI, 1.1–1.3; P=0.003) and fetal intrauterine death (OR, 5.9; 95% CI, 1.8–19.4; P=0.003) were risk factors for severe acute pancreatitis. Conclusions: Pre-delivery acute respiratory distress syndrome and gestational week were independent risk factors for fetal death. Fetal intrauterine death and gestational week were independent risk factors for severe acute pancreatitis.